Lard as a suitable and cheap substrate for microbial lipids production by Yarrowia lipolytica - Lopes, Marlene (2015)
[Excerpt] Current agricultural and industrial practices have led to the generation of large amounts of various low-value or negative cost crude wastes, which are difficult and economically notattractive to treat and valorize. One important example of waste generation is animal fat, commonly found in tanning process and slaughterhouses. These wastes, in which the lipids are often the main and most problematic components, are not currently used effectively and there are almost no application methods to recover the respective value. (...)